Contradictory Discourses of Motherhood as Institution and Experience - Haratyan, Farzaneh (SARE: Southeast Asian Review of English, 2017)
Feminists agree that patriarchal discourses have subordinated mothers and constrained them to the private sphere by tying them to the domestic role of reproduction, by over-emphasizing womenÂ’s physical and biological capability of reproduction, nurturing and child rearing (with the two last features being falsely positioned as a purely female ability) through the notions of ideal and perfect mothering. Women’s actual physical and mental capabilities and the biological difference between men and women are over-emphasized by patriarchal power relations to normalize false ideologies that women are naturally suited for the domestic roles of mothering and reproduction. Judith Buler’s theorization of gender and performativity after the Foucaldian model acts as a resistant discourse against dominant power structures, to challenge the way discourse enacts gender ordering and roles. Performativity forms identity through the reiterative practice of discourse produced by power relations (Butler, 2009, 2010). A focus on gendered identities is central to current theorizations of gender as socially and discursively constructed, a continual process of negotiation and modification.